Biorregulador, inoculação com azospirillum brasilense, doses de nitrogênio nos componentes de rendimento e qualidade de sementes de milho - Piccinin, Gleberson Guillen (2015)
The objective of the work was to evaluate the agronomic efficacy of seed inoculation with Azospirillum brasilense associated with nitrogen doses and handling with bioregulator on agronomic performance, yield and seeds physiological quality of corn culture. Experiments were conducted in the simple hybrid maize Pioneer 30F35 YH in the agricultural years 2010/2011 and 2011/2012 at the Experimental Farm of Iguatemi that belongs to the State University of Maringá. Treatments were constituted in the absence and presence of seed inoculation with bacteria of the Azospirillum brasilense species in the liquid formulation, nitrogen fertilization doses (0.0, 45, 90, 135 and 180 kg of N ha-1) applied to the base and top-dressing, in association with foliar application of bioregulator (0.0 and 250 mL ha-1) in the V4 stage. The experimental design used was in randomized complete blocks with six replications, in factorial scheme (2 x 5 x 2). Facing results it is possible to infer that seed treatment with inoculant did not influence the plant height and number of grain rows. The use of inoculant does not fully replace the nitrogen fertilization in corn. The interaction between the application of 250 mL ha-1 of bioregulator in V4 and seed inoculation with Azospirillum brasilense did not provide significant increments in yield. Inoculation with Azospirillum brasilense in seeds provided increments of 11% in productivity, followed by the increase in grain number per row and leaf nitrogen content. Inoculation of corn seeds provided returns of R$ 303.00 ha-1. Increasing N rate can contribute to the improvement of the physiological quality of maize seed. The application of 113 kg ha-1 of N positively affects seed germination, expressed by the first count of germination and by the modified cold test. Oil, protein, and nitrogen contents in the seeds have changed positively, depending on nitrogen rates. The application of 250 mL ha-1 of bioregulator did not affect germination as well as oil, protein and nitrogen content of corn seeds.